Myocardial Injury in Patients With Sepsis and Its Association With Long-Term Outcome. Issue 2 (February 2018) - Frencken, Jos F.; Donker, Dirk W.; Spitoni, Cristian; Koster-Brouwer, Marlies E.; Soliman, Ivo W.; Ong, David S.Y.; Horn, Janneke; van der Poll, Tom; van Klei, Wilton A.; Bonten, Marc J.M.; Cremer, Olaf L.; de Beer, Friso M.; et al.
Abstract : Background: Sepsis is frequently complicated by the release of cardiac troponin, but the clinical significance of this myocardial injury remains unclear. We studied the associations between troponin release during sepsis and 1-year outcomes. Methods and Results: We enrolled consecutive patients with sepsis in 2 Dutch intensive care units between 2011 and 2013. Subjects with a clinically apparent cause of troponin release were excluded. High-sensitivity cardiac troponin I (hs-cTnI) concentration in plasma was measured daily during the first 4 intensive care unit days, and multivariable Cox regression analysis was used to model its association with 1-year mortality while adjusting for confounding. In addition, we studied cardiovascular morbidity occurring during the first year after hospital discharge. Among 1258 patients presenting with sepsis, 1124 (89%) were eligible for study inclusion. Hs-cTnI concentrations were elevated in 673 (60%) subjects on day 1, and 755 (67%) ever had elevated levels in the first 4 days. Cox regression analysis revealed that high hs-cTnI concentrations were associated with increased death rates during the first 14 days (adjusted hazard ratio, 1.72; 95% confidence interval, 1.14–2.59 and hazard ratio, 1.70; 95% confidence interval, 1.10–2.62 for hs-cTnI concentrations of 100–500 and >500 ng/L, respectively) but not thereafter. Furthermore, elevated hs-cTnI levels were associated with the development of cardiovascular disease among 200 hospital survivors who were analyzed for this end point (adjusted subdistribution hazard ratio, 1.25; 95% confidence interval, 1.04–1.50). Conclusions: Myocardial injury occurs in the majority of patients with sepsis and is independently associated with early—but not late—mortality, as well as postdischarge cardiovascular morbidity. Abstract : Supplemental Digital Content is available in the text.